2018
DOI: 10.1186/s12711-018-0414-x
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of runs of homozygosity islands in cattle caused by interference with copy number variation or large intermarker distances

Abstract: BackgroundRuns of homozygosity (ROH) islands are stretches of homozygous sequence in the genome of a large proportion of individuals in a population. Algorithms for the detection of ROH depend on the similarity of haplotypes. Coverage gaps and copy number variants (CNV) may result in incorrect identification of such similarity, leading to the detection of ROH islands where none exists. Misidentified hemizygous regions will also appear as homozygous based on sequence variation alone. Our aim was to identify ROH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…The chromosome-wide coverage varies between 1% on BTA24 and 10% on BTA12 (Additional file 2: Table S4 and Additional file 1: Figure S2). Compared to other cattle CNV studies conducted using the same SNP array and the genome assembly UMD3.1 [22,24,[29][30][31][32], our CNV discovery results are in a similar range (Additional file 2: Table S5).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The chromosome-wide coverage varies between 1% on BTA24 and 10% on BTA12 (Additional file 2: Table S4 and Additional file 1: Figure S2). Compared to other cattle CNV studies conducted using the same SNP array and the genome assembly UMD3.1 [22,24,[29][30][31][32], our CNV discovery results are in a similar range (Additional file 2: Table S5).…”
Section: Resultssupporting
confidence: 65%
“…We further inspected BTA12:70-77 MB region where a large change between UMD3.1 and ARS-UCD1.2 was observed. This region was reported to have a large number deletion and duplication calls by other cattle CNV studies based on UMD3.1, regardless of the studied breeds [24,[29][30][31][32][33]. In our CNV discovery, we identified 7 CNVRs (total length of~6.2 Mb) in this region based on UMD3.1, whereas ARS-UCD1.2 based results revealed 9 CNVRs that cov-ered~1 Mb.…”
Section: Resultsmentioning
confidence: 51%
“…The chromosome-wide coverage varies between 1% on BTA24 and 10% on BTA12 (Table S4 and Figure S2). Compared to other cattle CNV studies conducted using the same SNP array and the genome assembly UMD3.1 [22,24,[29][30][31][32], our CNV discovery results are in a similar range (Table S5).…”
Section: Cnv Discovery In the Genome Build Ars-ucd12supporting
confidence: 68%
“…Moreover, a recent study demonstrated that a significant proportion of ROH islands or hotspots detected in the bovine genome are artifacts due to gaps in SNP coverage as well as to structural variations such as deletions (Nandolo et al . ).…”
Section: Discussionmentioning
confidence: 97%